A comparison of three student selection procedures in terms of efficiency - DECAESTEKER, Christoph (Institutional Knowledge at Singapore Management University, 2000)
In many countries the implementation of a selection/admission system as a gatekeeper to enter higher education is surrounded by controversy. This study examines three possible selection/admission procedures (i.e., no admission exam: N = 495; admission exam with cognitive ability and situational tests: N = 1245; admission exam with achievement, cognitive ability and situational tests: N = 915) in terms of efficiency. Efficiency was defined as the extent to which so-called true positives are not selected in order to eliminate one true negative. The selection/admission procedure consisting of cognitive ability and situational tests was found to be most efficient.